L-DOPA-Induced Dyskinesia and Abnormal Signaling in Striatal Medium Spiny Neurons: Focus on Dopamine D1 Receptor-Mediated Transmission - Feyder, Michael; Bonito Oliva, Alessandra; Fisone, Gilberto (Frontiers in Behavioral Neuroscience, 2011)
Dyskinesia is a serious motor complication caused by prolonged administration of L-DOPA to patients affected by Parkinson’s disease. Accumulating evidence indicates that L-DOPA-induced dyskinesia (LID) is primarily caused by the development of sensitized dopamine D1 receptor (D1R) transmission in the medium spiny neurons of the striatum. This phenomenon, combined with chronic administration of L-DOPA, leads to persistent and intermittent hyperactivation of the cAMP signaling cascade. Activation of cAMP signaling results in increased activity of the cAMP-dependent protein kinase (PKA) and of the dopamine and cAMP-dependent phosphoprotein of 32 kDa (DARPP-32), which regulate several downstream effector targets implicated in the control of the excitability of striatal MSNs. Dyskinesia is also accompanied by augmented activity of the extracellular signal-regulated kinases (ERK) and the mammalian target of rapamycin complex 1 (mTORC1), two signaling pathways involved in the control of transcriptional and translational efficiency. Pharmacological or genetic interventions aimed at reducing abnormal transduction at the level of these various signaling cascades have been shown to attenuate LID in different animal models. For instance, LID is reduced in mice deficient for DARPP-32, or following inhibition of PKA. Blockade of ERK obtained genetically or using specific inhibitors is also able to attenuate dyskinetic behavior in rodents and non-human primates. Finally, administration of rapamycin, a drug which blocks mTORC1, results in a strong reduction of LID. This review focuses on the abnormalities in signaling affecting the D1R-expressing MSNs and on their potential relevance for the design of novel antidyskinetic therapies.